ANALISIS KUALITAS FISIK DAN BAKTERIOLOGI AIR BERSIH PERUSAHAAN DAERAH AIR MINUM DESA SELANBAWAK TABANAN - I Nyoman Jirna (Meditory : The Journal of Medical Laboratory, 2022)
ABSTRACTIntroduction: PDAM water Selanbawak village is water used by people at Selanbawak Village for their daily needs such as drinking water. Drinking water qualify the requirements of physics, microbiology, chemistry and radioactivity (Permenkes 492 of 2010). In 2020 there occur a landslide disaster which cause damage to pipes, causing health problems such as diarrhea. Methods: The research used quantitative with a descriptive design using the simple random sampling technique of 179 populationsThe study was conducted to determine the quality of clean water from PDAM based on physical and bacteriological parameters from January to April 2021 at the homes of the residents of Banjar Selanbawak kaja, then physical and bacteriological examinations using the Most Probable Number (MPN) method were carried out at  Panureksa Utama Laboratory. Results: The results of physical quality from 15 samples (100%) qualify the health requirements based on Permenkes RI No. 492 / MENKES / PER / IV / 2010. Meanwhile, examination of Coliform bacteria (67%) with the category fulfilling the health requirements and examination of Escherichia coli bacteria (73%) with the category fulfilling the requirements based on Permenkes RI No. 492 / MENKES / PER / IV / 2010. Conclusion: Based on these results, it can be concluded that most of the PDAM water still qualify health requirements.Keywords: Selanbawak, physical, bacteriology, PDAM water